2013
DOI: 10.2478/pjvs-2013-0007
|View full text |Cite
|
Sign up to set email alerts
|

The effect of experimental low zearalenone intoxication on ovarian follicles in pre-pubertal bitches

Abstract: Companion animals, including bitches, may be exposed to zearalenone (ZEN) toxins that are often present in feed, and ZEN intoxication may lead to ovarian dysfunction. This study involved evaluation of the degree of ZEN-induced hypo stimulation of ovary by determination of proliferative and apoptotic indices and description of the ultra-structural organization of ovarian follicles in pre-pubertal bitches subjected to experimental, long-term exposure to low-dose ZEN mycotoxicosis. The experiment involved 30 cli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 23 publications
1
20
0
Order By: Relevance
“…The above has been confirmed by the results of our unpublished study (Gajęcka 2013) which determined apoptotic and proliferative indices of ovarian follicles in the same bitches. Intensified apoptosis and slower proliferation were observed in primordial and primary follicles in both oocytes and in follicular cells.…”
Section: Discussionsupporting
confidence: 77%
“…The above has been confirmed by the results of our unpublished study (Gajęcka 2013) which determined apoptotic and proliferative indices of ovarian follicles in the same bitches. Intensified apoptosis and slower proliferation were observed in primordial and primary follicles in both oocytes and in follicular cells.…”
Section: Discussionsupporting
confidence: 77%
“…ZEN blocks ERs or mimics steroid hormones, in particular estradiol (Brevini et al 2005). Even at very low concentrations, ZEN and its metabolites stimulate cell proliferation sensitive tissues in various animal species, which is consistent with principles of hormesis (Frizell et al 2011, Gajęcka et al 2011, Gajęcka 2013. At concentrations below NOAEL (threshold values), many toxic compounds, including undesirable substances such as ZEN, exert stimulating/adaptive effects (Heberer et al 2007, Dobrzański andFornalski 2011), but these effects are weaker than those in organisms not exposed to a given toxic substance.…”
Section: Discussionmentioning
confidence: 58%
“…The study of ZEN by Gajecka [8] found that, ZEN can suppress the proliferative activity of follicle cells contained in the ovarian cortex. The decline in follicular cells count was not followed with oocyte maturation process and follicular liquor influx that physiologically fills the antral space in the de Graaf’s follicle before ovulation process.…”
Section: Discussionmentioning
confidence: 99%